General Analysis of Mycobacterium Tuberculosis and its repercussion on the Covid-19 pandemic: A Literature Review (Research, Society and Development, 2022)
Developmental viral infections have led to pandemics, causing large-scale morbidity and mortality. Tuberculosis and the important COVID-19 have characteristics that predispose cross-sectional control exercises. Both are infectious diseases that could be happening together in the human body. In this context, the objective of the study was to carry out a review of the literature regarding the relationship between Mycobacterium Tuberculosis and the Sars-CoV-12 virus during the pandemic. As a methodological approach, articles published between 2021 and 2021 were used, which are only available in the following databases: Virtual Health Library (BVS), LILACS/Pub, SciELO and Google Scholar. Tuberculosis and Covid-19 are comprehensive warnings with their high transmissibility. They are similar diseases that have specific characteristics. Despite the severity of the Sarv-cov-2 virus acting together with tuberculosis, it remains a concern, mainly because it affects social minorities worldwide, generating social problems such as inequality and social exclusion. Because they are altered diseases and manifest as aerosols, it is necessary to adopt protective measures such as the use of mask and social distance in order to prevent these diseases. It is concluded that since the beginning of the coronavirus pandemic, cases of tuberculosis and COVID-19 have occurred simultaneously, and the diagnosis is difficult to perform due to the proximity of signs and symptoms between these diseases.